Dynamic Tensile Strength of Dry and Saturated Hard Coal under Impact Loading - Xianlei Zhu; Qing Li; Guihua Wei; Shizheng Fang (Energies, 2020)
To evaluate the influence of water content on the hard coal dynamic behavior, the dynamic tensile properties of saturated coal Brazilian disk (BD) samples were studied using a split Hopkinson pressure bar system, and dry samples were also tested as a control group. In the range of impact speeds studied, the tensile strength of the saturated coal is lower than that of the dry specimen. A synchronized triggering high-speed camera was used to monitor the deformation and failure process of dry and saturated coal samples, allowing analysis of the failure stages and mechanism of dynamic BD test, the broken mode was classified into three types, which can be classified into unilateral tensile failure, bilateral or multilateral tensile failure, and shear failure. Finally, fragments smaller than 5 mm in diameter were statistically analyzed. There is less debris in range of 0−5.0 mm for the saturated coal sample than for the dry coal. This study provides some information about the dynamic response of the hard coal for the relevant practical engineering.